Assessment of scale-up parameters of microwave-assisted extraction via the extraction of flavonoids from cocoa leaves - Chan, Chung Hung; Yusoff, Rozita; Ngoh, Gek Cheng (Wiley, 2015)
Microwave-assisted extraction (MAE) is a promising technique for the extraction of flavonoid compounds from plants. However, it is difficult to scale up due to the complex mass transfer involved. This has prompted the study of parameters for scaling up the system by considering energy-related parameters, i.e. the nominal power density and the absorbed power density (APD). Modeling of MAE of flavonoid compounds from cocoa (Theobroma cacao L.) leaves using the film theory model was performed for this purpose. Operating parameters such as the sample particle size, the solvent-to-feed ratio, and the microwave irradiation power were also included in the kinetic study. The APD exhibited its aptitude as scaling-up parameter as it can characterize both the extraction kinetics and the extraction yields of MAE. Furthermore, it can be used as a reference for predicting the optimum extraction time of MAE under various heating conditions.